Chronic pain epidemiology – where do lifestyle factors fit in? - van Hecke, Oliver (Br J Pain, 2013)
Chronic pain is common and complex and has a large impact on individuals and society. Good epidemiological pain data provide key information on the use of resources (both in general practice and in specialist clinics), insight into factors that lead to or favour chronicity and the design of interventions aimed at reducing or preventing the effects of chronic pain. This review aims to highlight the important factors associated with chronic pain, including those factors which are amenable to lifestyle intervention.